WHAT IS SMART ABOUT CONTROLLING ELECTRIC ENERGY SYSTEMS? VIRTUAL POWER PLANTS AND THE DIGITIZATION OF THE GRID - Katja Müller (International Journal of Innovative Technologies in Social Science, 2025)
Energy systems are said to be subject to a twin transition of decarbonisation and digitization. Virtual power plants are one part of creating the much proclaimed smart grid, situated at the intersection of electricity production and the electricity transmission. This paper investigates how virtual power plants work by showing their interrelation with the electricity market and the grid. With a focus on the German and European electricity system, the research shows that the market comes first and physic electricity feed-in second. Based on a market ideal, virtual power plants act as an aggregating tool for decentralized energy production and as a regulatory device reacting to supply and demand, albeit the programmes cannot rule out the risk of working against grid stability.